Immunogenic characteristics of Avibacterium paragallinаrum (serogroup B) isolates and strains - M. S. Firsova; V. A. Yevgrafova; A. V. Potekhin; R. V. Yashin; O. V. Pruntova; V. S. Russaleyev (Ветеринария сегодня)
Infectious disease of chickens caused by the bacterium Avibacterium paragallinarum remains one of the urgent problems of the poultry industry, as evidenced by numerous reports of recurrent infectious coryza outbreaks in chickens around the world. Bacteriological tests performed in 2014–2019 demonstrated that the disease caused by Avibacterium рaragallinarum (serogroup B) is endemic in the Russian Federation. The paper presents the results of tests for immunogenic properties of antigens of 13 infectious coryza isolates recovered from the pathological material delivered to the FGBI “ARRIAH” from poultry farms of the Russian Federation and the Republic of Belarus. For this, samples of the vaccine containing formalin-inactivated Avibacterium paragallinarum cells and an oil adjuvant were prepared. The poultry was immunized followed by challenge with homologous and heterologous isolates. The degree of manifestation of the disease clinical signs was assessed according to the method proposed by V. E. Soriano. The vaccine sample based on the antigen of the ApB08 isolate induced an insufficient immune response in poultry when infected with the ApB04 and ApB12 isolates. Conversely, a high level of animal protection was demonstrated when infected with the ApB08 isolate. ApB04, ApB08 and ApB12 isolates were comprehensively studied, identified as the most promising for production of vaccines against infectious coryza in chickens, and deposited in the FGBI “ARRIAH” Microorganism Strain Collection under numbers 1116, 5111 and 1818, respectively. Also, a comparative assessment of potency of the experimental vaccine and two commercial products against infectious coryza, including antigens of strains No. 1116, 5111 and 1818, was performed. The experimental vaccine demonstrated maximum protection against infection with Avibacterium рaragallinarum homologous strains.